Kesalahan Newman Dalam Menyelesaikan Soal Cerita SPLDV Ditinjau Dari Tingkat Kecemasan Matematika Siswa Kelas IX SMPN 6 Mataram - Sofie Atma Dwiva; Sri Subarinah; Eka Kurniawan (FKIP Universitas Mataram, 2026)
The perception of mathematics as a difficult subject often leads students to make errors. Errors made by students when solving story problems need to be analyzed to determine the cause. Mathematics anxiety is one of the causes of students making errors. This study aims to describe the errors made by students of SMPN 6 Mataram in answering story problems based on Newman's theory in terms of students' level of mathematics anxiety. The type of research used is qualitative. The research instruments used were anxiety level questionnaires, story problem tests, and interview guidelines. The selection of subject in class IX F used a purposive sample with the criteria: (1) students who had learned the system of linear equations in two variables (SPLDV), (2) students who had completed the mathematics anxiety questionnaire, (3) students from one class representing high, moderate, and low levels of mathematics anxiety. The results show that mathematics anxiety influences the types of errors students make in solving SPLDV word problems. Students with high anxiety made errors in comprehension, transformation, process skills, and conclusion stages; those with moderate anxiety in comprehension, process skills, and conclusion; while students with low anxiety mainly erred at the conclusion stage.